THE HISTORY AND CURRENT ACTIVITIES OF THE EVANGELICAL CHRISTIAN BAPTIST COMMUNITY IN FERGANA REGION (Scientific journal of the Fergana State University, 2024)
In this article, people belonging to different religions have been living in the regions of our country since ancient times, religious tolerance has always been a priority in the regions, in particular, representatives of the Evangelical Christian Baptist community have entered the territory of Uzbekistan, settled down and performed their prayers safely. It is explained on the example of the evangelical Christian Baptist community in Fergana region.